Impulsivity in the self-harm and suicidal behavior of young people: A systematic review and meta-analysis. (September 2019) - McHugh, Catherine M.; Chun Lee, Rico Sze; Hermens, Daniel F.; Corderoy, Amy; Large, Matthew; Hickie, Ian B.
Abstract: Background: Impulsivity is considered a possible phenotype underlying the expression of self-harm and suicidal behaviors. Yet impulsivity is a not a unitary construct and there is evidence that different facets of impulsivity follow different neurodevelopmental trajectories and that some facets may be more strongly associated with such behaviors than others. Moreover, it is unclear whether impulsivity is a useful predictor of self-harm or suicidal behavior in young people, a population already considered to display heightened impulsive behavior. Methods: A systematic review and meta-analysis of studies published in Medline, PubMed, PsychInfo or Embase between 1970 and 2017 that used a neurocognitive measure to assess the independent variable of impulsivity and the dependent variable of self-harm and/or suicidal behavior among young people (mean age < 30 years old). Results: 6183 titles were identified, 141 full texts were reviewed, and 18 studies were included, with 902 young people with a self-harm or suicidal behavior and 1591 controls without a history of these behaviors. Deficits in inhibitory control (13 studies, SMD 0.21, p-value = 0.002, 95% confidence interval (CI) (0.08–0.34), prediction interval (PI) = 0.06–0.35) and impulsive decision-making (14 studies, SMD 0.17, p-value = 0.008, 95% CI (0.045–0.3), PI = 0.03–0.31) were associated with self-harm or suicidal behavior. There were no significant differences between measures of different facets of impulsivity (ie. delay discounting, risky decision-making, cognitive or response inhibition) and self-harm or suicidal behavior. Conclusion: Multiple facets of impulsivity are associated with suicidal behavior in young people. Future suicide research should be designed to capture impulsive states and investigate the impact on different subtypes of impulsivity.